Related Factors with Addition Mother's Weight During Pregnant in the Work Area Public health center Belimbing, Padang City - Ester Pakpahan; Vaulinne Basyir; Nur Indrawaty Lipoeto; Masrul; Bobby Indra Utama; Firdawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Weight gain during pregnancy is an important indicator in predicting morbidity and mortality in babies and mothers. One important factor in pregnancy is the nutritional status of the pregnant woman which will have an impact on the mother and fetal growth. Factors related to weight gain in pregnant women cannot be separated from behavioral factors possessed by each individual. The aim of this research is to determine the factors associated with maternal weight gain during pregnancy in the Belimbing Community Health Center Working Area, Padang City. The design of this research is quantitative research, the research method used